Agricultural Land Management to Increase Crop Production in Waimital Village, Kairatu District, West Seram Regency - Ohorella, Indah Sevia; Salakory, Melianus; Riry, Johan (GEOFORUM, 2025)
Effective agricultural land management plays a crucial role in improving crop production and farmers' welfare. This study aims to analyze the factors affecting agricultural productivity in Waimital Village, Kairatu District, West Seram Regency. The research method employed a quantitative approach with multiple linear regression analysis to measure the relationship between land management variables and agricultural yield. The findings indicate that the use of organic fertilizers, efficient irrigation systems, and crop rotation positively impact harvest outcomes. Furthermore, limited access to technology and agricultural extension services remain significant challenges for farmers in increasing productivity. Therefore, government and academic interventions are required to accelerate the adoption of modern agricultural technologies. This study concludes that optimizing land management can enhance food security and farmers' well-being in a sustainable manner.